Agriculture drainage affects river water quality - Ayob, Katimon; Azraai, Kassim; Fadil, Othman; Johan, Sohaili; Zulkifli, Yusop; Normala, Hashim (The Institution of Engineers, Malaysia, 2011)
Link to publisher's homepage at http://www.myiem.org.my/